PROPAGANDA IN THE DIGITAL ERA: THE INFLUENCE OF SOCIAL MEDIA ON PUBLIC OPINION - Renisa, Reza; Kheisa, Adinda Febriana; Purba, Budiman (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2024)
The development of social media is very rapid as time goes by, because over time technology will increasingly develop. One of the functions of social media is to connect one party to another party, but as time goes by, the function of social media is not only to connect one party to another party, but with social media public opinion can be changed and even adjusted to the interests of the party starting the provocation. the. Every human being has interests and these interests are the key to everything, from these interests other functions of social media emerge. Propaganda in this digital era has many roles in political issues in Indonesia.